Overcoming Learning Barriers in Faraid Education for Improved Student Outcomes - Kurniawan, Fahdulloh; Haryanto , Budi (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Pondok Pesantren (Islamic boarding schools) are vital for character and knowledge development in Indonesia, especially in the study of faraid (Islamic inheritance law). Specific Background: At Wali Barokah Islamic Boarding School in Kediri City, students face obstacles such as ineffective teaching methods, limited resources, and challenges in understanding Arabic texts. Knowledge Gap: Existing research has not thoroughly analyzed these specific barriers and their impact on learning outcomes. Aims: This study identifies the obstacles faced in faraid education and offers strategic recommendations for improvement. Results: Using qualitative methods, the research reveals that methodological issues, insufficient materials, and rigid teaching styles significantly hinder student understanding and motivation. Novelty: This study provides a comprehensive analysis of the barriers affecting faraid learning. Implications: It highlights the need for adaptive teaching methods and improved resources to enhance student engagement and comprehension, ultimately fostering competent graduates in accordance with Islamic law. Highlights: Ineffective Teaching Methods: Predominantly traditional approaches lead to student disengagement and reduced comprehension. Language Challenges: Difficulties in understanding Arabic texts hinder students' ability to grasp complex concepts in faraid. Resource Limitations: Insufficient learning materials negatively impact the applicability and relevance of the knowledge acquired by students. Keywords: Faraid Knowledge, Islamic Boarding School, Learning Obstacles, Teaching Methods, Student Motivation